A Closer Look at Women’s Electoral Participation in the 2024 General Election in Garut Regency - Damayanti, Sri (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2024)
This research is motivated by the organization of the 2024 elections, which have been conducted annually within Indonesia's democratic system since the inception of independence. In practice, the execution of the democratic system via these elections has failed to effectively uphold democratic values within the government of the state and nation. The persistently low participation of female voter groups in the Pangatikan District, Garut Regency, during all phases of the 2024 general election is obvious. The employed research method is qualitative, utilizing an analytical descriptive approach to examine the object's condition in its natural state. The descriptive technique functions as a problem-solving approach that analyzes a subject or study object by depicting its current situation based on factual representation. The data gathering methods employed are direct observation and direct communication through interviews during the 2024 general election in the Pangatikan District, Garut Regency. According to the analysis of the examined concerns, the research findings comprise, The involvement of women's groups in the organizing of all phases of the 2024 general election in the Pangatikan District, Garut Regency, remains suboptimal. This is evident among female voters who possess knowledge of the general election's organization yet fail to actively participate and engage ideally in the 2024 electoral process. Factors affecting female voter participation in the 2024 general election in the Pangatikan District encompass political motivation from election organizers, the individual traits of the female voter demographic, the prevailing social characteristics in the Pangatikan District, and the evolving political landscape in the Pangatikan District, Garut Regency. Initiatives to augment female voter participation in the Pangatikan District, Garut Regency, for the 2024 general election encompass socialization activities regarding the election, the establishment of democracy volunteers to promote engagement and enhance voter quality, educational programs for first-time voters and female voter groups, and the amplification of mass media's role in disseminating information about the entire electoral process and its stages. Keywords: Participation, Voters, Women, General Election